Financial Technology and SME Resilience in the Digital Economy: A Comprehensive Literature Review - Astri Ayu Purwati; Zulfadli Hamzah; Mazzlida Mat Deli (Research in Accounting Journal (RAJ), 2025)
The rapid development of digital technologies has transformed the financial landscape and created new opportunities for Small and Medium-Sized Enterprises (SMEs) to improve their access to financial services and enhance business performance. This study aims to systematically review the existing literature on digital financial inclusion, FinTech adoption, and SME performance to identify major research trends, synthesize empirical findings, and propose future research directions. The study employed a Systematic Literature Review (SLR) approach based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Relevant articles published between 2015 and 2025 were collected from reputable academic databases, including Scopus, Web of Science, ScienceDirect, Emerald Insight, SpringerLink, Taylor & Francis, and MDPI. A total of 20 selected studies were analyzed using thematic synthesis techniques. The findings reveal that digital financial inclusion and FinTech adoption significantly contribute to SME growth, operational efficiency, financial accessibility, innovation capability, and business sustainability. Digital financial inclusion enables SMEs to overcome traditional financing barriers by facilitating access to digital financial services, while FinTech adoption improves financial management, transaction efficiency, and alternative financing opportunities. Furthermore, the review highlights the important roles of financial literacy, technological readiness, organizational capability, and government support in promoting successful digital finance adoption. Despite these benefits, challenges such as digital literacy limitations, cybersecurity risks, technological infrastructure constraints, and regulatory uncertainties continue to impede broader implementation. The study also identifies several research gaps, particularly regarding the integration of emerging technologies such as artificial intelligence, blockchain, and big data analytics within SME financial ecosystems. The findings provide valuable insights for researchers, policymakers, financial institutions, and business practitioners seeking to promote sustainable SME development through digital financial transformation.